Evolution of the Inner Accretion Flow and the White Dwarf Spin Pulse during the 2023 Outburst in GK Persei - Mariko Kimura; Takayuki Hayashi; Yuuki Wada; Wataru Iwakiri; Shigeyuki Sako; Martina Veresvarska; Simone Scaringi; Noel Castro-Segura; Christian Knigge; Keith C. Gendreau; Zaven Arzoumanian (The Astrophysical Journal)
We present our X-ray and optical observations performed by NICER, NuSTAR, and Tomo-e Gozen during the 2023 outburst in the intermediate polar GK Persei. The X-ray spectrum consisted of three components: blackbody (BB) emission of several tens of eVs from the irradiated white dwarf (WD) surface, a source possibly including several emission lines around 1 keV, and multitemperature bremsstrahlung emission from the accretion column. The 351.3 s WD spin pulse was detected in X-rays, and the observable X-ray flux from the column drastically decreased at the off-pulse phase, which suggests that the absorption of the column by the accreting gas, called the curtain, was the major cause of the pulse. As the system became brighter in the optical, the column became fainter, the pulse amplitude became higher, and the energy dependence of pulses became weaker at <8 keV. These phenomena could be explained by the column’s more pronounced absorption by the denser curtain as mass-accretion rates increased. The BB and line fluxes rapidly decreased at the optical decline, which suggests the expansion of the innermost disk edge with decreasing accretion rates. The electron scattering or the column geometry may be associated with the almost no energy dependence of high-energy pulses. The irradiated vertically thick structure at the disk may generate optical quasi-periodic oscillations with a period of ∼5700 s.